2014
DOI: 10.1186/1471-2202-15-8
|View full text |Cite
|
Sign up to set email alerts
|

Previous infection with Staphylococcus aureusstrains attenuated experimental encephalomyelitis

Abstract: BackgroundBacterial superantigens are potent T cell activators that can activate T cells with specificity for antigens of the central nervous system (CNS). In this study, we compared the effect of two S. aureus strains on experimental autoimmune encephalomyelitis (EAE) development. C57BL/6 female mice were infected with S. aureus ATCC 51650, which produces toxic shock syndrome toxin 1 (TSST-1+) or S. aureus ATCC 43300, which does not produce toxins (TOX-). Three days later, the animals were subjected to EAE in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The total prevalence of sea , seb , sec , sed , seg and sei genes in the S. aureus isolates of MS exacerbation patients were 30%, 11.11%, 15.55%, 4.44%, 1.11% and 1.11%, respectively. Higher prevalence of superantigens and enterotoxigenic genes, in the patients who suffered from MS, were reported previously by Mulvey et al ( 4 ), Franca et al ( 7 ) and Kumar et al ( 27 ).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The total prevalence of sea , seb , sec , sed , seg and sei genes in the S. aureus isolates of MS exacerbation patients were 30%, 11.11%, 15.55%, 4.44%, 1.11% and 1.11%, respectively. Higher prevalence of superantigens and enterotoxigenic genes, in the patients who suffered from MS, were reported previously by Mulvey et al ( 4 ), Franca et al ( 7 ) and Kumar et al ( 27 ).…”
Section: Discussionsupporting
confidence: 70%
“…Enterotoxigenic genes of the S. aureus can activate a high proportion of T cells, due to their ability to bind to both major histocompatibility complex (MHC) molecules in antigen presenting cells and specific V-β regions, in the T cell receptor ( 4 , 7 ). This activation results in the polyclonal stimulation of T cells and an increased production of proinflammatory cytokines ( 4 , 7 ). Based on the controversial theories and the results of previous studies, the enterotoxigenic genes of S. aureus may be involved in the fundamental etiology of multiple sclerosis (MS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 This indicates that the effect of infection on EAE development is associated with either acute or chronic inflammatory responses. It is interesting to note that recent data failed to show exacerbation of EAE severity by other infections: Franca et al 32 showed that preceding infection with Staphylococcus aureus actually decreases EAE clinical scores; Another study showed that infection with Taenia crassiceps also led to attenuation of EAE. 33 In both studies, the infections led to Th2 immunologic characteristics response.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental autoimmune encephalomyelitis (EAE) has been extensively used to elucidate the pathophysiology and the potential therapeutic measures applied to MS (Franc¸a et al, 2014;Zorzella-Pezavento et al, 2014;Rahimi et al, 2015). Current therapeutic approaches to control the destructive immune response in autoimmune disease are mainly based on non-specific drugs that systemically suppress the function of many immune effector cells.…”
Section: Introductionmentioning
confidence: 99%